Exploring the Necessity of Advancing the Construction of Information Management in Real Estate Management - Zhu, Enhao (Transactions on Economics, Business and Management Research, 2024)
With the continuous progress of socio-economic development, the real estate industry has experienced rapid growth. As a leading industry in China, the importance of this sector is self-evident. However, due to objective factors, real estate management faces many challenges, such as poor information management and sharing, difficulties in market regulation and supervision, and insufficient risk prevention and resolution capabilities. To address these issues, it is particularly necessary to promote the construction of information management in real estate management. Information management construction, through strengthening the construction of information infrastructure, building a unified information management system, and promoting the integration of information technology and business processes, can significantly improve the efficiency and level of real estate management. Specifically, information management construction can achieve real-time data updating and sharing, break the phenomenon of information silos, optimize business processes, reduce manual operations, and lower the error rate. Through data analysis and mining, it provides strong support for decision-making, enhancing the scientific nature and accuracy of decisions. Over time, it effectively improves the efficiency and level of real estate management, providing a strong guarantee for the healthy development of the industry.